Direct assessment of protection operation and non-viable transients. - Singh, C. (IEEE Transactions on power systems)
The transients induced in power systems by a large disturbance can initiate unexpected events such as protection operation or converter misfiring. This paper proposes a direct technique for assessing the likelihood of such events. The approach is based on Lyapunov (energy) function methods, but with the critical energy redefined to take account of protection operating characteristics and viability constraints. Power systems have many protection devices and many constraints that must be monitored. The paper provides a method of identifying the subset of protection devices and/or viability constraints that are most vulnerable for any particular disturbance. Controlling UEP (unstable equilibrium point) ideas underlie the algorithm